KEBIJAKAN PENGEMBANGAN WISATA DAN PENATAAN KAWASAN WISATA MASJID AGUNG DEMAK DAN MAKAM KESULTANAN DEMAK BINTORO OLEH PEMERINTAH KABUPATEN DEMAK PERIODE 2007 - Adam Harindra P; Turtiantoro .; Susilo Utomo (Journal of Politic and Government Studies, 2013)
In this study, researchers wanted to know how tourism development policy efforts and the arrangement of the tourist area of the Great Mosque and the Tomb of the Sultanate of Demak Bintoro as a site of pilgrimage tourism and heritage sites Demak kingdom imposed by local government Demak, and has the objective to know how tourism development policy efforts and arrangement of the tourist area of the Great Mosque and the Tomb of the Sultanate of Demak Bintoro is by Demak Regency. The study focused on policies owned by the government bureaucracy which is the vehicle of regional heads towards the expected results for the whole policy area in which these policies were later implemented by the concerned agencies namely the Department of Tourism and Culture of Demak District.In this study, using qualitative research methods of descriptive research that describes the properties of an individual, symptoms, circumstances, a phenomenon that can be words, pictures, and not a number. The goal is to solve a problem, said, analyze, classify and compare to the conclusion later. This study attempts to analyze how tourism development policy and arrangement of the tourist area of the Great Mosque and the Tomb of the Sultanate of Demak Bintoro period of 2007 conducted by the District Demak government. The results of research conducted on tourism development policies and structuring the tourist area of the Great Mosque and the Tomb of the Sultanate of Demak Bintoro can be concluded that the policy process is already well under development, although still lacking and the stage of the development and evaluation of tourism management Demak Mosque and the Tomb of the Sultanate of Demak Bintoro own. while the policy arrangement of the tourist area of the Great Mosque and the Tomb of the Sultanate of Demak Bintoro not run well because of some problems and irregularities arise that appear after the relocation of the arrangement of tourist area, thus causing potential will not be optimal, not on target and expectations.Advice can be given is the government supposed to be more consistency maintenance and relocation of the post patrol arrangement is not a tourist area that requires more than just discipline the officer, but a careful and strategic arrangementsKeywords: Policy, Tourism Development, Structuring tourist area.